2005
DOI: 10.1063/1.1840102
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of mechanically polished ZnO

Abstract: The effects of mechanical polishing on the photoluminescence (PL) from each polar face of wurtzite-structure ZnO are presented. Differences observed for the 4.2K PL of a mechanically polished surface when compared to that of a chemomechanically polished surface include broadened bound-exciton peaks, hot-exciton luminescence, and a donor-acceptor pair peak at 3.2108eV. Analysis of this donor-acceptor pair peak results in estimated donor and acceptor ionization energies of 52±10 and 230±10meV, respectively, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…These differences can arise from the crystal growth process itself, but also from the polishing step [6]. The concentration of the NRRCs is higher in the AFRL sample, as deduced from the significantly lower luminescence emission compared with the TD sample.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…These differences can arise from the crystal growth process itself, but also from the polishing step [6]. The concentration of the NRRCs is higher in the AFRL sample, as deduced from the significantly lower luminescence emission compared with the TD sample.…”
Section: Resultsmentioning
confidence: 92%
“…This strong variability suggests that it could be related to defects. In fact, its origin is a matter of controversy; it has been associated with the first LO phonon replica of the free exciton; it is 72 meV away the FXA exciton peak [6]; a donor acceptor pair (DAP) transition [16]; a free to neutral acceptor (e-A1) band [17]; from an exciton bound to extended defects (dislocations) [17]. Recent results around the Vickers indentations have revealed that this band is complex [18], and can consist of two subbands overlapping each other, peaking around 3.31 and 3.29 eV, respectively, which were associated with an exciton bound to a point defect, P D , and the one LO phonon replica of the free exciton, FX-1LO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the non-polar materials, the high density of dislocations is responsible for the point defects as Zn vacancy (V Zn ) and oxygen interstitial (O i ) [22]. Ulrike also demonstrated the presence of point defects V Zn in non-polar ZnO materials by high-resolution scanning tunneling microscopy measurement [16].…”
Section: Article In Pressmentioning
confidence: 97%
“…The dependence of ZnO exciton luminescence on dislocation density is, therefore, an actual question, which is intensively studied [9−14]. In ZnO crystals, films and ceramics, such dislocation-induced effects as the quenching of initially present luminescence [9, 11−14] as well as the appearance of new luminescence bands [10,13] were observed. In the present paper, the influence of dislocations on ZnO room temperature exciton luminescence intensity and spectrum shape has been found.…”
mentioning
confidence: 99%